Relationship between composition, antioxidant capacity and phenolic content of feed concentrate for dogs - Restrepo B., Giovanni (2019)
Oxidative stress has been associated with the development of many chronic and degenerative diseases in canines. The presence of antioxidants in food contributes to the reduction of the harmful effects of reactive oxygen species (ROS) and nitrogen (RNS). Polyphenols are a group of substances with high antioxidant activity and play an important role in the prevention of diseases. The aim of this study was to evaluate the relationship between the composition, the antioxidant capacity and the polyphenol content of dog feeds from different commercial segments. Nineteen dog foods from four commercial segments: popular, economic, premium and super premium were randomly selected. Through a bromatological analysis the composition of each feed was evaluated. Total antioxidant capacity (TAC) and total phenolic content (TFC) were measured through the ABTS and Folin-Ciocalteu methods, respectively. Analysis of variance and correlation were performed. Dog feeds of the premium and super premium segments presented higher proportions of crude protein and fat, and lower crude fiber, ash, calcium and phosphorus, in comparison with feeds of the popular and economic segments (p<0.05). For the popular, economic, premium and super premium segments, TFC values of 160.1 ± 49.8, 146.7 ± 41.5, 131.6 ± 21.5 and 144.9 ± 34.1 mg of gallic acid/100 g of sample and CAT values of 3146.0 ± 564.5, 2895.4 ± 581.0, 2837.6 ± 241.7 and 2875.79 ± 325.8 μmol Trolox/L sample were determined, respectively (p>0.05). A positive correlation was found between crude fiber content and TFC (r = 0.47, p<0.05). It is concluded that commercial segmentation of the dog feeds is not reflected in its antioxidant contribution and a higher crude fiber content, typical of feeds of the popular and economic segments, is positively associated with the content of phenols.